Optimalisasi Keuntungan Produksi Sayuran Di Desa Balunijuk Kabupaten Bangka Menggunakan Linear Programming - Humairah, Reni; Afrizal, Aidil Adrianda; Dwiyanti, Fahira (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2025)
Vegetable farming holds considerable potential, offering high economic returns for farmers and remaining a feasible agricultural pursuit. This study was designed to analyze profit optimization in vegetable farming through systematic production analysis. The research subjects were vegetable farmers in Balunijuk Village, Bangka Regency. Specifically, the objectives are to determine the optimal vegetable production combination, calculate the maximum achievable profit (Z) under resource constraints, and evaluate resource slack to compare optimal and actual production conditions. Profit optimization was examined using the simplex method of linear programming, enabling the identification of optimal resource allocation and the maximization of farmers’ income. Primary data were collected from farmers in Balunijuk Village through structured interviews, covering one planting season. The dataset represents cross-sectional observations of land use, capital, labor, and production outputs. The findings indicate that Balunijuk Village, despite being a center of vegetable farming, has not yet achieved optimal production. Under optimal conditions, resource utilization changes significantly: labor and capital become binding constraints, while land exhibits surplus capacity. The optimization process reallocates land use by reducing water spinach cultivation and expanding mustard greens, thereby increasing profit by 42.97%.